Efek Teratogenik Sinar X - Arif Faisal Arif Faisal (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
The application of X-rays in the medical field has positive and negative effects. The effects of X-ray radiation to the intrauterine embryo and foetus depend on the period of gestation. In the first trimester the embryo may be resorbed and aborted and may also be born with serious defects. In the late trimester radiation may cause less serious defects and it may disturb the function of organs. Many defects involve nerve names and are associated with symptoms of mental retardation.To prevent radiation exposure to embryo and foetus, it is necessary to observe the "ten -day rule", when X -ray examination is performed. The threshold doses for embryo and foetus are still unknown.Key Words: physical deformity - mental retardation - radiobiology - radiation injury - teratogenic effect